Innominate Interim Measures and the Moral Crisis of Lawyers in Colombia - Mojica Figueroa, Luis Antonio (DIXI, 2016)
Introduction: Starting with the research problem, a doctrinal study was carried out to explain the regulation and evolution of the Colombian legal system, as well as its requirements, in order to achieve better understanding of innominate interim measures. Methodology: With statistical analysis of disciplinary proceedings against lawyers—in contrast to the number of graduates in law and related filds—the study seeks to demonstrate the moral crisis of lawyers in Colombia. Results: Thre is a warning that this moral crisis could weaken extrajudicial conciliation as a procedural requirement within civil procedure. In this article, basic concepts such as the request, order, and implementation of an interim measure are studied. Similarly, the apparent diffrence between each of these procedural stages is explained, as their understanding leads to ready comprehension of the existing procedural diffilty. Conclusions: Based on the fidings presented, an amendment is proposed to the fist paragraph of Article 590 of Law 1564 of 2012, which allows any misuse of innominate interim measures to be countered when complying with extrajudicial conciliation as a procedural requirement.